22P Early changes in plasma cell-free DNA (cfDNA) as a predictive biomarker of immune checkpoint inhibitors (ICIs) efficacy. (15th December 2019) - Garcia, I Matos; Moreno, A; Arenillas, C; Carbo, C Hierro; Munoz-Cosuelo, E; Martin-Liberal, J; Braña, I; Villar, M Vieito; Azaro, A; Gadea, O Saavedra Santa; Gonzalez, I Gardeazabal; Javier, R; et al.
Abstract: Background: The role of cfDNA-based analyses in the management of patients (pts) receiving ICIs is still poorly understood. We have implemented a translational program to systematically obtain blood samples of pts receiving ICIs in phase I clinical trials for cfDNA monitoring. Methods: Since August 2018, 92 pts were prospectively included and baseline blood samples and prior to every cycle were collected. Plasma cfDNA was isolated using QIAamp Circulating Nucleic Acid Kit and measured using Qubit fluorometer. DNA fragments length and profile were assessed using Agilent 2100 Bioanalyzer. Pts with baseline and prior to cycle 2(preC2) blood samples and at least 1 tumor assessment have been included in the analysis. We established 2 groups based on variations of cfDNA levels on preC2 related to baseline: 1) cfDNA progression group as increase (>0% cfDNA change) 2) cfDNA response group as decrease (<0% cfDNA change). We analysed the correlation between longitudinal changes in cfDNA with progression free survival (PFS) and clinical benefit (partial response or stable disease as best response). PFS was calculated using Kaplan-Meier method, long rank test was used for statistical comparison and chi-square for categorical variables. Results: 92 pts with different advanced tumor types were included. Median number of previous lines was 2.38. Median time from baseline cfDNA to preC2 was 22.82 days and from preC2 to first tumor assessment was 32.18 days. PFS in the cfDNA response group (38 pts) was higher compared with cfDNA progression group (54 pts); median 4.87 m (3.11 – 6.62) and 3.0 m (2.24-3.76), respectively (HR = 0.49 [0.28-0.86] p < 0.001). Clinical benefit was higher in the cfDNA response group (66%) as compared to cfDNA progression group (44%), chi‐square p < 0.04 No difference was observed in median baseline cfDNA levels between pts with PD as best response (28.12 ng/ml) and pts with clinical benefit (19.76 ng/ml) p = 0.28. Conclusion: The monitoring of early changes of cfDNA levels is a fast approach to predict response to ICI therapy in our cohort. Further validation of these results and correlation with circulating tumor DNA is ongoing. Legal entity responsible for the study: The authors. Funding: This research has been partially funded by the Comprehensive Program of Cancer Immunotherapy & Immunology (CAIMI), supported by the Banco Bilbao Vizcaya Argentaria Foundation (BBVA Foundation) - Grant 9/2017. Disclosure: C. Hierro Carbo: Research grant / Funding (self): Bayer; Honoraria (self): Ignyta; Honoraria (self), Travel / Accommodation / Expenses: Lilly; Honoraria (self), Travel / Accommodation / Expenses: Roche. J. Martin-Liberal: Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Roche; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Novartis; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: MSD; Honoraria (self), Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: Ipsen; Travel / Accommodation / Expenses: Pierre Fabre; Honoraria (self): Bristol-Myers Squibb; Travel / Accommodation / Expenses: Astellas. I. Braña: Speaker Bureau / Expert testimony, Research grant / Funding (self): Bristol-Myers Squibb; Speaker Bureau / Expert testimony, Research grant / Funding (institution): AstraZeneca; Research grant / Funding (self): Regeneron; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): GSK; Research grant / Funding (institution): Incyte; Speaker Bureau / Expert testimony, Research grant / Funding (self): Orion Pharma; Research grant / Funding (institution): Merck Serono; Research grant / Funding (self): Celgene; Research grant / Funding (self): Janssen; Research grant / Funding (self): Kura; Research grant / Funding (institution): Pfizer. M. Vieito Villar: Travel / Accommodation / Expenses: Roche. E. Elez: Speaker Bureau / Expert testimony: MSD; Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Sanofi; Speaker Bureau / Expert testimony, Research grant / Funding (self): Merck Serono; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Amgen; Speaker Bureau / Expert testimony: Servier. E. Felip: Speaker Bureau / Expert testimony: ABBVIE; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy: Blueprint; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Advisory / Consultancy: Celgene; Advisory / Consultancy: Guardant; Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony: Takeda; Advisory / Consultancy: Janssen. R. Dienstmann: Advisory / Consultancy: Roche; Advisory / Consultancy: Novartis; Research grant / Funding (self): Merck Serono; Advisory / Consultancy: Symphogen; Advisory / Consultancy, Speaker Bureau / Expert testimony: Amgen; Advisory / Consultancy: Sanofi; Advisory / Consultancy: IPSEN; Advisory / Consultancy: Astellas. A. Gros: Research grant / Funding (institution): Novartis. J. Tabernero: Advisory / Consultancy: Array; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Bayer; Advisory / Consultancy: Beigene; Advisory / Consultancy: Boehringer; Advisory / Consultancy: Chugai; Advisory / Consultancy: Genetech; Advisory / Consultancy: Genmab; Advisory / Consultancy: Halozyme; Advisory / Consultancy: Roche; Advisory / Consultancy: Inflection Bioscience; Advisory / Consultancy: IPSEN; Advisory / Consultancy: Kura; Advisory / Consultancy: Lilly; Advisory / Consultancy: Menarini; Advisory / Consultancy: MSD; Advisory / Consultancy: Merck; Advisory / Consultancy: Merrimarck; Advisory / Consultancy: Merus; Advisory / Consultancy: Molecular Partners. E. Garralda: Advisory / Consultancy: ROCHE; Advisory / Consultancy: Ellipses; Advisory / Consultancy: Neomed; Advisory / Consultancy: Janssen; Advisory / Consultancy: Boehringer; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): MSD; Advisory / Consultancy: Bristol-Myers Squibb. All other authors have declared no conflicts of interest.